The impact of an invasive plant changes over time - Dostál, Petr; Müllerová, Jana; Pyšek, Petr; Pergl, Jan; Klinerová, Tereza (Ecology letters, 2013)
Many exotic plant invaders pose a serious threat to native communities, but little is known about the dynamics of their impacts over time. In this study, we explored the impact of an invasive plant Heracleum mantegazzianum (giant hogweed) at 24 grassland sites invaded for different periods of time (from 11 to 48 years). Native species' richness and productivity were initially reduced by hogweed invasion but tended to recover after ~30 years of hogweed residence at the sites. Hogweed cover declined over the whole period assessed. A complementary common garden experiment suggested that the dynamics observed in the field were due to a negative plant-soil feedback; hogweed survival and biomass, and its competitive ability were lower when growing in soil inocula collected from earlier-invaded grasslands. Our results provide evidence that the initial dominance of an invasive plant species and its negative impact can later be reversed by stabilising processes.
Keywords: půdní mikrobiologie; čas; Animals; ekosystém; Poaceae; Time; Ecosystem; Heracleum; zvířata; Introduced Species; bolševník; zavlečené druhy; lipnicovité; Soil Microbiology